Compllete handyman do-it-yourself encyclopedia : a complilation of special interest projects and manual for the repair and care of homes, autos, appliances, hobby equiipment. VI dimmer-electricity (H.S. Stuttman Co, 1975)
777-930 p.; 25 cm.